2023
DOI: 10.1021/acs.jctc.3c00814
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Molecular Modeling and Machine Learning for Drug Design

Song Xia,
Eric Chen,
Yingkai Zhang

Abstract: Modern therapeutic development often involves several stages that are interconnected, and multiple iterations are usually required to bring a new drug to the market. Computational approaches have increasingly become an indispensable part of helping reduce the time and cost of the research and development of new drugs. In this Perspective, we summarize our recent efforts on integrating molecular modeling and machine learning to develop computational tools for modulator design, including a pocket-guided rational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 259 publications
0
8
0
Order By: Relevance
“…Indeed, it was previously demonstrated that coarse models of the first solvation shell could cause huge inaccuracy in determining pKa [ 5 ]. Further, several attempts were made in re-shaping the “reaction centre” with encouraging results [ 1 , 2 , 3 , 4 , 5 , 8 ]. Therefore, to better understand if the difference in pKa values obtained with different functionals could be related with a significant modification of the solvation cavity, an extensive analysis was performed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it was previously demonstrated that coarse models of the first solvation shell could cause huge inaccuracy in determining pKa [ 5 ]. Further, several attempts were made in re-shaping the “reaction centre” with encouraging results [ 1 , 2 , 3 , 4 , 5 , 8 ]. Therefore, to better understand if the difference in pKa values obtained with different functionals could be related with a significant modification of the solvation cavity, an extensive analysis was performed.…”
Section: Resultsmentioning
confidence: 99%
“…The computational determination of pKa is usually performed through several methodologies, varying from the pioneering “machine learning” approach, to the more traditional physicochemical-inspired models. The former is focused on the quantitative structure–activity relationship (thereafter QSAR), but although it generally requires huge computational costs, it has not yet shown good reliability [ 4 ]. The latter relies on solid computational methods [ 5 , 6 ] that can be classified into two categories: (i) the “indirect” approach, which exploits a thermodynamic cycle that takes into consideration the energy at equilibrium of the deprotonated species in the gas and in the solution phase; (ii) the “direct” approach, in which the ionogenic equation in water is explicitly considered [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its success underscores the need for further research on MolFeSCues compatibility with a variety of pretrained models, including those from different paradigms. Moreover, the integration of molecular dynamics simulations and machine learning, as evidenced by recent advances in computational tools for drug design, suggests an alternative avenue for improving model accuracy in specific scenarios ( Xia et al 2023 ). These methods combine physical principles with machine learning, and may provide superior outcomes by enhancing small molecule representation learning and efficient exploration of chemical space.…”
Section: Discussionmentioning
confidence: 99%
“…We have observed a skyrocketing increase of ML applications in theoretical and computational chemistry in the past decade, involving all space-time domains in Figure a. To most people, applying ML to theoretical and computational chemistry is merely taking advantage of a new tool to expediate the simulation and improve the accuracy.…”
Section: Machine Learning As a New Paradigmmentioning
confidence: 99%
“…In the recent theoretical and computational chemistry literature, we have witnessed a gigantic growth of applications of artificial intelligence, machine learning (ML), and deep learning (hereafter, we do not distinguish these terminologies from each other and generally refer to them as ML). We also started noticing booming theoretical and computational chemistry publications using quantum computers (QC). These newly developed methodologies are fascinating, and their impacts could be far-reaching.…”
Section: Introductionmentioning
confidence: 99%